Development of an e-module in the form of a flipbook on integrated Islamic circulatory system material for grade XI SMA/MA - Fitriani Isma; Ayatusa'adah Ayatusa'adah; Nanik Lestariningsih (HAFECS PRESS, 2023)
Islamic-integrated learning has been carried out in several subjects in Madrasahs, but students still need encouragement to live it. Islamic-integrated teaching materials are required to facilitate solving these problems. This research was conducted because of the need for teaching material to be able to help students in the learning process either independently at home or guided by educators at school, so this study aims to describe the validity and response of educators and students to products in the form of e-modules in the form of flipbook material developed Islamic integrated circulatory system. The method used in this research is research and development (R&D) using the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). The subjects of this study were expert/expert validators, educators, and students. The data collection technique used was a questionnaire given to experts/experts to find out the validity of the product, and a response questionnaire was given to educators and students to find out the response to the product being developed. The results of this study indicate that the product validity of experts, namely material experts, obtained a percentage of 89.25% with very valid criteria, media experts obtained a percentage of 96.75% with very valid criteria, and interpreters obtained a percentage of 78.62%. The results of the teacher's response were 92.25% with very good criteria, and student responses received a percentage of 79.75% with good criteria. Based on these results, the e-module in the form of a flipbook on Islamic integrated blood circulation system material can be stated to be very valid and good for use in school learning. Abstrak. Pembelajaran yang terindegrasi dengan keislaman sebenarnya sudah dilaksanakan dalam beberapa mata pelajaran di Madrasah, namun peserta didik masih perlu dorongan untuk menjiwainya. Bahan ajar yang terintegrasi keislaman diperlukan untuk memfasilitasi penyelesaian masalah tersebut. Penelitian ini dilakukan karena diperlukannya sebuah bahan ajar untuk dapat membantu peserta didik dalam proses pembelajaran baik secara mandiri di rumah maupun dibimbing oleh pendidik di sekolah, sehingga penelitian ini bertujuan untuk mendeskripsikan kelayakan serta respon pendidik dan peserta didik terhadap produk berupa e-module berbentuk flipbook materi sistem peredaran darah terintegrasi keislaman yang dikembangkan. Metode yang digunakan dalam penelitian ini adalah penelitian dan pengembangan (R&D) dengan menggunakan model pengembangan ADDIE (Analysis, Design, Development, Implementation, dan Evaluation). Subjek penelitian ini yakni validator ahli/pakar, serta pendidik dan peserta didik. Teknik pengumpulan data yang digunakan adalah angket yang diberikan kepada pakar/ahli untuk mengetahui kelayakan produk, dan angket respon diberikan kepada pendidik serta peserta didik untuk mengetahui respon terhadap produk yang dikembangkan. Hasil penelitian ini menunjukkan bahwa kelayakan produk para pakar ahli yakni ahli materi memperoleh persentase 89,25% dengan kriteria sangat layak, ahli media memperoleh persentase 96,75% dengan kriteria sangat layak dan ahli tafsir memperoleh persentase 78,62%. Hasil respon pendidik memperoleh persentase 92,25% dengan kriteria sangat baik dan respon peserta didik memperoleh persentase 79,75% dengan kriteria baik. Berdasarkan hasil tersebut maka e-module berbentuk flipbook materi sistem perdaran darah terintegrasi keislaman dapat dinyatakan sangat layak dan baik untuk digunakan dalam proses pembelajaran di sekolah.